studi terbaru tentang film - Ridho Kurniawan (STKIP Muhammadiyah Muara Bungo, 2019)
Nowadays learning languages has become more important. Learning a new language not only develops individual intelligence, but also it gives learners, permission to enter and gets learners near to another culture and prepares them with the essential skills to succeed and change their behavior. There are many ways to increase our English skill, such as listening to the music, reading a lot, playing games, watching movies, writing story etc. One of that way is watching movies, watching movies not only to fill the spare time or get rid the boredom, but also can get some lesson especially English lesson. We can learn their pronunciation, spelling, grammar and also we can get many new vocabularies from the movies. Through movie the students will feel excited and did not get bored easily especially watch their favorite movies. This paper aims to propose the use of movies at high school by discussing relevant theories regardig the use of movies at senior high school for EFL learner.